Constraint versus restraint in the body mass dynamics during moult of a species with precocial young. (17th April 2020) - Van Dellen, Amanda W.; Riecke, Thomas V.; Leach, Alan G.; Nicolai, Christopher A.; Person, Brian T.; Lemons, Patrick R.; Eichholz, Michael W.; Lindberg, Mark S.; Schamber, Jason L.; Herzog, Mark P.; Sedinger, James S.
Abstract : Body mass declines during wing moult in numerous, but not all, populations of Anatidae. We assessed two leading hypotheses for body mass dynamics during wing moult: (1) body mass dynamics are adapted to attain a target body mass at the end of wing moult (restraint hypothesis) vs. (2) body mass dynamics reflect environmental constraint on the nutrient–energy balance during wing moult (constraint hypothesis). We used regressions of mass of breeding female Black Brant Branta bernicla nigricans on ninth primary length (a measure of moult stage) for each of 16 years to assess mass dynamics during wing moult and used regression equations to predict mass at the beginning and end of wing moult each year. We also included gosling mass at 30 days (an indicator of forage availability) in models of adult mass to assess how mass dynamics varied as a function of foraging conditions. Predicted body mass (± 95% CI) at the start of wing moult (ninth primary = 0 mm) varied significantly among years from 1032 ± 52 to 1169 ± 27 g. Similarly, predicted mass in late wing moult (ninth primary = 142 mm) ranged from 1048 ± 25 to 1222 ± 28 g. The rate of mass gain was significantly related to gosling mass at 30 days: interaction between adult ninth primary length and gosling mass = 0.0031 ± 0.0020 ( P  = 0.003). Females initiated wing moult at lower body masses, gained mass more rapidly and ended with wing moult heaviest when goslings were heaviest. Body mass dynamics of female Black Brant during wing moult were consistent with the constraint hypothesis. The positive association between gosling mass and rate of body mass gain by adult females during wing moult was also consistent with the constraint hypothesis.